2003
DOI: 10.1152/ajpheart.00916.2002
|View full text |Cite
|
Sign up to set email alerts
|

Coronary blood flow regulation in exercising swine involves parallel rather than redundant vasodilator pathways

Abstract: In dogs, only combined blockade of vasodilator pathways [via adenosine receptors, nitric oxide synthase (NOS) and ATP-sensitive K+ (KATP) channels] results in impairment of metabolic vasodilation, which suggests a redundancy design of coronary flow regulation. Conversely, in swine and humans, blocking KATP channels, adenosine receptors, or NOS each impairs coronary blood flow (CBF) at rest and during exercise. Consequently, we hypothesized that these vasodilators act in parallel rather than in redundancy to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
76
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(84 citation statements)
references
References 50 publications
7
76
1
Order By: Relevance
“…Therefore, the authors [49] concluded 573 that the primary mechanism of the ATP-mediated vasodilation is 574 vascular hyperpolarization via activation of the K IR channels. 575 It should be stated, however, that some earlier studies question 576 the role of ATP as a factor controlling coronary blood flow during 577 exercise (in the absence of ischemia) [77,78]. Additionally, some 578 studies involving a single-leg knee-extensor exercise of submaxi-579 mal intensity as an exercise model have failed to demonstrate 580 significant changes in plasma ATP concentration despite signifi-581 cant alterations in blood O 2 content and limb blood flow in humans 582 [121,122].…”
mentioning
confidence: 99%
“…Therefore, the authors [49] concluded 573 that the primary mechanism of the ATP-mediated vasodilation is 574 vascular hyperpolarization via activation of the K IR channels. 575 It should be stated, however, that some earlier studies question 576 the role of ATP as a factor controlling coronary blood flow during 577 exercise (in the absence of ischemia) [77,78]. Additionally, some 578 studies involving a single-leg knee-extensor exercise of submaxi-579 mal intensity as an exercise model have failed to demonstrate 580 significant changes in plasma ATP concentration despite signifi-581 cant alterations in blood O 2 content and limb blood flow in humans 582 [121,122].…”
mentioning
confidence: 99%
“…PO 2crit increases in most MCT rats, and correlates with the expression of HIF 1α in nuclei of cardiomyocytes. The upper value of PO 2crit is similar to coronary sinus PO 2 during maximum exercise, 20 hPa (swine: Merkus et al, 2003;dog: Tune et al, 2004). End capillary venous PO 2 in the RV myocardium of MCT rats is not known.…”
Section: Hypoxic Cores In Hypertrophied Cardiomyocytesmentioning
confidence: 66%
“…Moreover, neither arterial, nor coronary venous plasma endothelin-levels are altered during exercise [75]. However, withdrawal of endothelininduced vasoconstriction contributes to recruitment of flow reserve in response to exercise [70,75] and preliminary data suggest that the responsiveness of the coronary vasculature to endothelin is reduced. This reduction in coronary responsiveness to endothelin is mediated through NO and prostacyclin [77], which are known to be able to induce post-translational modification of the endothelin receptors [78] and may therefore result in altered signal transduction.…”
Section: Merkus Signals From Cardiac Myocytesmentioning
confidence: 97%
“…Studies in vivo confirm a role for endothelin in exercise hyperemia (see also below), but do not show a change in the vasodilator influence of adenosine during exercise [74,75], while the role of H 2 O 2 still needs to be confirmed. Signals from the endothelium: The endothelium produces both vasodilators (NO and prostacyclin) and vasoconstrictors (endothelin).…”
Section: Merkus Signals From Cardiac Myocytesmentioning
confidence: 97%
See 1 more Smart Citation